Borrowed words a history of loanwords in English - Durkin, Philip (Oxford Oxford University Press, 2014)
"The rich variety of the English vocabulary reflects the vast number of words it has taken from other languages. These range from Latin, Greek, Scandinavian, Celtic, French, Italian, Spanish, and Russian too, among others, Hebrew, Maori, Malay, Chinese, Hindi, Japanese, and Yiddish. Philip Durkin's full and accessible history reveals how, when, and why. He shows how to discover the origins of loanwords, when and why they were adopted, and what happens to them once they have been."--Publishers website.
Introducing concepts -- Introducing the data -- Historical and cultural background to c.1150 -- Very early borrowings into Germanic -- Old English in contact with Celtic -- An overview of Latin loanwords in Old English -- Interrogating the data from chapter 6 -- Methodologies : sound change; word geography; loanwords versus semantic borrowing -- Introduction to Scandinavian loanwords in English -- Identifying Scandinavian borrowings and assessing their impact -- Exploring the contact situation and identifying loans -- Quantifying French and Latin contributions to Middle English -- Example passages from English and multilingual texts -- Borrowing from Latin and French after 1500 -- Loanwords from other languages : test cases -- Long-term effects of loanwords on the shape of the English Lexicon -- General conclusions and pointers for further investigation.
Includes bibliographical references (pages 429-454) and indexes.
Keywords: English language -- Etymology; Comparative linguistics